Dudziro : interrogating the visions of religious beliefs - Zimbabwe Pavilion, Venice (Milano : Charta, 2013)
Zvavahera, Portia; Thebe, Voti; Jogee, Rashid; Chihota, Virginia; Mathison, Michele.
55th International Art Exhibition, La Biennale di Venezia 2013
Catalogue to accompany the exhibition held in the Zimbabwe Pavilion in Venice for the 55th Venice Biennale, 01.06.2013 -24.11.2013
boek